An exploration of midwives' role in the promotion and provision of antenatal influenza immunisation: A mixed methods inquiry. Issue 1 (February 2021) - Smith, Susan Elizabeth; Gum, Lyn; Thornton, Charlene
Abstract: Problem: No South Australian study has previously investigated the role of midwives in the promotion and provision of antenatal influenza immunisation. Background: Influenza acquired in pregnancy can have serious sequalae for both mother and foetus. Recent studies have demonstrated that influenza vaccine in pregnancy is both safe and effective. Despite this, evidence suggests that vaccine uptake in pregnancy is suboptimal in both Australia and worldwide. Aim: The aim of this study was to investigate the role of midwives in the promotion and provision of antenatal influenza vaccine and, to provide a statistical and thematic description of the barriers and enablers midwives encounter. Methods: This mixed method study incorporated a cross sectional on-line survey and in-depth interviews conducted with midwives, employed in urban and regional South Australia. Findings: Quantitative data were available for 137 midwives and 10 midwives participated in the interviews. Recruitment for the interview phase was through the last question on the survey. Whilst all midwives indicated that education and vaccine promotion were part of their role, immunisation knowledge varied between Registered Nurse/Midwives (RM/RN) 80% and Registered Midwives (RM) 48.90% ( p = 0.001). Quantitative data showed that only 43% of midwives felt sufficiently educated to provide the vaccine. Midwives who had received formal immunisation training were more likely to recommend the vaccine 93.7% ( p = 0.001). Qualitative data confirmed these results and identified the lack of immunisation education as a barrier to practise. Conclusion: Midwives identified an immunisation knowledge deficit. Midwives who had received immunisation education were more likely to actively promote and provide the vaccine to pregnant women. These findings indicate the need for more immunisation education of midwives in both tertiary and practice settings.